One-pot chemo-enzymatic conversion of D-xylose to furfuralcohol by sequential dehydration with oxalic acid plus tin-based solid acid and bioreduction with whole-cells. (November 2018) - Xue, Xin-Xia; Ma, Cui-Luan; Di, Jun-Hua; Huo, Xiao-Yu; He, Yu-Cai
Graphical abstract: Highlights: Relationship between pKa of organic acid and TOF of co-catalysis was explored. Oxalic acid (pKa = 1.25) gave the maximum TOF value (6.26 h −1 ). Furfural was synthesized from D- xylose with oxalic acid plus SO4 2− /SnO2 -argil. High furfural yield (50.8%) from D- xylose (50 g/L) was achieved. An effective approach for one-pot synthesis of FOL from D -xylose was demonstrated. Abstract: In this study, organic acid could be used as co-catalyst for assisting solid acid SO4 2− /SnO2 -argil to convert hemicellulose-derived D -xylose into furfural. The relationship between pKa of organic acid and turnover frequency (TOF) of co-catalysis with organic acid plus SO4 2− /SnO2 -argil was explored on the conversion of D- xylose to furfural. Oxalic acid (pKa = 1.25) (0.35 wt%) was found to be the optimum co-catalyst for assisting SO4 2− /SnO2 -argil (3.6 wt%) to synthesize furfural from D- xylose (20 g/L) at 180 °C for 20 min, and the furfural yield and TOF could be obtained at 57.07% and 6.26 h −1, respectively. Finally, the obtained furfural (107.6 mM) could be completely biotransformed to furfuralcohol by recombinant Escherichia coli CCZU-K14 whole-cells at 30 °C and pH 6.5 in the presence of 1.5 mol glucose/mol furfural and 400 mM D -xylose. Clearly, this strategy shows high potential application for the effective synthesis of furfuralcohol from biomass-derived D -xylose.